Effects of high flavanol dark chocolate on cardiovascular function and platelet aggregation - Gurvinder Rull; Julian Shiel; Martina H. Lundberg; David J. Collier; Atholl Johnston; Timothy D.Warner; Roger Corder; Zetty Nadia Mohd Zain (Elselvier, 2024)
Volume 71